Applying an external reduction potential to reduce the consumption of zinc powder during gold cementation. (January 2023) - Nie, Yanhe; Wang, Sen; Wang, Qiang; Chen, Jianghao; Jiang, Yunxiang
Graphical abstract: Highlights: A novel technique to reduce the zinc consumption for recovery Au(S2 O3 )2 3− was developed. The consumption of zinc powder can be reduced by 70% by using an applied potential. Leaching solution can be recycled after gold cementation. Abstract: One of the factors limiting the practical application of gold thiosulfate leaching is the inefficient recovery of Au(S2 O3 )2 3−, which can be recovered by cementation using active metals. In gold cementation, the application of electrochemical reduction on the solution can simultaneously reduce metal consumption, and meet the recycling requirements. By introducing an applied potential of 0.14 V to an 80 mL solution of 5 mM CuSO4, 0.5 M NH3, 0.1 M Na2 S2 O3, and 10 mg/L gold ion, the concentration of Cu(NH3 )4 2+ in the solution and the corresponding redox potential can be reduced from 5 mM to 0.261 mM, and 0.26 V to 0.06 V, respectively. Under these conditions, gold cementation was carried out, and the consumption of zinc powder was found to be reduced by 70%. By stirring for 12 h after the cementation, the concentration of Cu(NH3 )4 2+ in the solution can be recovered to 80% of the initial concentration resulting in redox potential of 0.23 V. Using this solution to leach gold ore, the gold leaching rate can reach 80% within 6 h, which meets the needs of requirements for dissolving gold in the leaching stage.